1990
DOI: 10.1111/j.1365-2141.1990.tb06327.x
|View full text |Cite
|
Sign up to set email alerts
|

Ras activation in myelodysplastic syndromes: clinical and molecular study of the chronic phase of the disease

Abstract: We studied N-ras and Ki-ras point mutations respectively at codons 12-13 and 12 in 15 patients with myelodysplastic syndromes (MDS) using the polymerase chain reaction (PCR) method for DNA amplification, and slot blot hybridization to allele specific oligonucleotide (ASO) probes. We analysed peripheral blood and bone marrow samples collected at diagnosis and repeatedly during the chronic phase of the disease to define when the activation occurred and in which haemopoietic cell populations, in order to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

1991
1991
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 21 publications
1
3
0
3
Order By: Relevance
“…We therefore longitudinally investigated ras gene m uta tion from MDS and AML by using a polymerase chain reaction (PCR) method. Like recent reports [9][10][11], we found a relatively high incidence of multiple point m uta tions of ras genes and also found diversity of such m uta tions during disease progression. Since somatic mutations of the ras gene have been postulated to serve as clonal markers of hematopoietic neoplasms [ 12], our cases carry ing multiple point mutations of the ras gene may help to understand the mechanisms of clonal evolution of myeloid neoplasms.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…We therefore longitudinally investigated ras gene m uta tion from MDS and AML by using a polymerase chain reaction (PCR) method. Like recent reports [9][10][11], we found a relatively high incidence of multiple point m uta tions of ras genes and also found diversity of such m uta tions during disease progression. Since somatic mutations of the ras gene have been postulated to serve as clonal markers of hematopoietic neoplasms [ 12], our cases carry ing multiple point mutations of the ras gene may help to understand the mechanisms of clonal evolution of myeloid neoplasms.…”
Section: Introductionsupporting
confidence: 70%
“…Several papers already described multiple point m uta tions of ras genes in MDS and AML [9][10][11]. In this study we commonly found multiple point mutations of ras genes (7 cases out of 19; table 2).…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, analysis by ASRA will not be affected by double mutations on one allele, whereas they can interfere with analysis by A S 0 hybridization [20]. The presence of double mutations in N-ras appears be a general phenomenon in hematopoietic malignancies with reports in AML [l], ALL [21], MDS [6,22], and multiple myeloma [23], but their importance in the clinical course of these diseases has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Factors predicting shorter survival include older age, anemia, neutropenia, thrombocytopenia, high percentage of bone marrow blasts, extensive dyspoiesis, abnormal central clustering of immature precursors within the bone marrow (ALIP score), increased numbers of circulating CD34 cells [7-9, 11, 14-20], abnormal cytogenetics (particularly involving chromosomes 5 and 7) [21], secondary MDS, expression of the mdr-1 phenotype [22], and RAS oncogene mutations or activation [23][24][25][26]. The relevance of p53 mutations is under study [27].…”
Section: Introductionmentioning
confidence: 99%